Construction of teaching materials for learning the “spring motion” in apparatus gymnastics, focusing on the relationship between the “forward roll bridge” and “spring motion from a higher level” - Nakanishi, Hiroshi; Osedo, Kazuki; Kihara, Seiichiro; Kubo, Kenji (Taiikugaku kenkyu, 2017)
The purpose of this study was to develop effective plans for teaching students to “spring” by building lesson plans adopted the “forward roll bridge” (FRB) and analyzing the effectiveness of the lesson plans through their execution in classes.  Lessons in “spring motion from a higher level” (SMH), which were taught over 6 school hours in total, were conducted as part of the apparatus gymnastics unit in the period April 15—28th, 2016. The participants were 5th grade students (32 male, 31 female, 2 classes) at “F” elementary school, located in Hiroshima prefecture. These lessons were followed by the FRB lessons (10 school hours in total) developed for this study, in which the students learned the “spring motion with hip subduction, from a forward roll” (SHF), with the aim of accomplishing the SMH by landing on the ground. This elementary school employs a subject teacher system for all grades, and the students had already learned the “antenna bridge” (AB) and the FRB in the previous year.  The results of this study were as follows:  (1) An improvement of the students' athletic skills when performing the AB, FRB, and SMH moves was observed after the 6 school hour lessons. This confirmed that the lesson plans were effective for teaching SMH.  (2) A correlation between achieving FRB and SMH was found in the first lesson (|r|≦0.700, p<0.0001), suggesting that FRB should be learned before SMH for a higher achievement rate. After the 6th lesson, correlations between AB and FRB (|r|≦0.348, p<0.006) and between FRB and SMH (|r|≦0.440, p<0.0001) were found. This suggested that FRB was an effective move for connecting acquisition of AB and that of SMH.  (3) Qualitative analysis of the students' movements indicated that there were 2 types of students who were unable to perform SMH: those who achieved SHF but could not do the spring, and those who could not achieve SHF. This differs from former studies that highlighted only the latter type of students. Therefore, it appears that the main difficulties of SMH are that students 1) need to achieve 2 skills, SHF and “pushing with hands,” and 2) need to adapt themselves to another situation in order to be able to accomplish the move.